VIETNAMESE STUDENTS’ PROBLEMS IN THEIR USE OF CHINESE IDIOMS AND SUGGESTIONS FOR IMPROVEMENT - Hien, Nguyen Dinh (VNU Journal of Foreign Studies; Vol 35 No 2, 2019)
Idioms are an important part of the lexicon in all languages, and in modern Chinese vocabulary in particular. They are fixed phrases, normally comprising 4 syllables (4 characters), and have been used extensively. The use of idioms improves the efficiency of expression, making sentences concise with profound implications. The use of Chinese idioms not only shows the users’ level of language proficiency, but also reflects their understanding of Chinese history, culture, country, people and society. The results of our survey of students’ written tests show that only a very small number of Chinese idioms are used, and misuse of idioms is very common. Having analyzed the mistakes and identified the causes, the paper offers suggestions on how to learn idioms to help Vietnamese students master and use Chinese idioms correctly.